GE_GERICHTE P/13650/2016 vom 20. März 2018 - GE Cour de justice (2018)
TORT MORAL ; LÉSION CORPORELLE ; DÉLIT MANQUÉ ; VIOLENCE CONTRE LES AUTORITÉS ; ASSIGNATION À RÉSIDENCE ; EXPULSION(DROIT PÉNAL) | CP.122; CP.123; CP.22.al1; CP.285.al1; CP.66.letabis; LEtr.119.al1; CO.47